1688 : the first modern revolution - Pincus, Steven C. A. (Lewis Walpole series in eighteenth-century culture and history., 2009)
Historians have viewed England's Glorious Revolution of 1688-1689 as an un-revolutionary revolution--bloodless, consensual, aristocratic, and above all, sensible. Steve Pincus refutes this traditional view. He demonstrates that England's revolution was a European event, that it took place over a number of years, and that it had repercussions in India, North America, the West Indies, and throughout continental Europe. His rich narrative, based on new archival research, traces the transformation of English foreign policy, religious culture, and political economy that, he argues, was the intended consequence of the revolutionaries of 1688-1689. James II's modernization program emphasized centralized control, repression of dissidents, and territorial empire. The revolutionaries, by contrast, took advantage of the new economic possibilities to create a bureaucratic but participatory state, which emphasized its ideological break with the past and envisioned itself as continuing to evolve. All of this, argues Pincus, makes the Glorious Revolution--not the French Revolution--the first truly modern revolution.--From publisher description.